Sexual behavior in the human female. - Pomeroy, Wardell B. (Wardell Baxter), 1913-2001 (Ishi Press International, 2010)
There are two Kinsey reports, one for the human male and one for the human female. This is the Second Part of "The Kinsey Report", the part that deals with the Human Female. This Report on the human female addresses the hot topics of when do girls start having sex and what percentage of all married women commit adultery. (The surprising answer is: About the same as the percentage of married men who commit adultery.) Because the Kinsey reports are lengthy, they have each been divided into two volumes here. Volume One of this book, "Sexual Behavior in the Human Female", is about the scope of the study, the problems of sampling, the sources of the data, and the types of sexual activity including pre-adolescent behavior, masturbation, nocturnal sex dreams, petting, pre-marital coitus and marital coitus. Volume Two deals with Extra-marital coitus, homosexual contacts, sex with animals, physiology of sexual response, psychology of sexual response and hormonal factors in sexual response, including studies on the castration of human males. Although this book was published in 1953 and it is assumed that our sexual mores have vastly changed since then, attempts to repeat the study by Dr. Kinsey have come up with about the same results.